Taking Books to the World : American Publishers and the Cultural Cold War - Laugesen, Amanda (University of Massachusetts Press, 2017)
Franklin Publications, or Franklin Book Programs, was started in 1953 as a form of cultural diplomacy. Until it folded in the 1970s, Franklin translated, printed, and distributed American books around the world, with offices in Egypt, Indonesia, Iran, Nigeria, Afghanistan, and Pakistan. Although it was a private firm, Franklin received funding from the United States Information Agency. This was an ambitious and idealistic postwar effort that ultimately became the victim of shifting politics. In Taking Books to the World, Amanda Laugesen tells the story of this purposeful enterprise, demonstrating the mix of goodwill and political drive behind its efforts to create modern book industries in developing countries. Examining the project through a clarifying lens, she reveals the ways Franklin's work aligned with cultural currents, exposing the imperial beliefs, charitable hopes, and intellectual reasoning behind this global experiment. --